2021
DOI: 10.1039/d1ra03675k
|View full text |Cite
|
Sign up to set email alerts
|

Increased sanitization potency of hydrogen peroxide with synergistic O3 and intense pulsed light for non-woven polypropylene

Abstract: By introducing synergistic elements to the VHP processes, potent sanitization of polymeric filters is achieved at low H2O2 concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Jeong et al used a combination of H 2 O 2 and O 3 at higher concentrations to obtain a complete disinfection in a chamber containing bacterial spore discs. 36 In our case, the combination of 0.2 ppm O 3 and 1 ppm H 2 O 2 led to a 1.3- and 1.8-fold enhancement compared to the individual O 3 and H 2 O 2 nebulisations, respectively. The viability reduction of the combination of 52 ppm TEG with 0.2 ppm O 3 was not different (67.5%) from the reduction produced by TEG alone, while the combination of 52 ppm TEG with 1 ppm H 2 O 2 resulted in a lower reduction (44.7%) as compared to individual TEG.…”
Section: Resultsmentioning
confidence: 44%
See 3 more Smart Citations
“…Jeong et al used a combination of H 2 O 2 and O 3 at higher concentrations to obtain a complete disinfection in a chamber containing bacterial spore discs. 36 In our case, the combination of 0.2 ppm O 3 and 1 ppm H 2 O 2 led to a 1.3- and 1.8-fold enhancement compared to the individual O 3 and H 2 O 2 nebulisations, respectively. The viability reduction of the combination of 52 ppm TEG with 0.2 ppm O 3 was not different (67.5%) from the reduction produced by TEG alone, while the combination of 52 ppm TEG with 1 ppm H 2 O 2 resulted in a lower reduction (44.7%) as compared to individual TEG.…”
Section: Resultsmentioning
confidence: 44%
“…33 The antimicrobial capacity of TEG could be due to its activity as a dehydrating agent. 34,35 TEG was found to be non-toxic even when the atmosphere is saturated with TEG, 33,36 and potential ecotoxicological effects are not reported. 37 Some authors have found that polyethylene glycol (PG), which is very similar to TEG from the chemistry standpoint, increases the uidity of the viral membrane showing a broad effect on enveloped viruses such as SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Usually, the antimicrobial action of metal ion-based coatings is limited due to the hindered transport of the encapsulated metal ions through the polymer layer to reach the adherent microbes on the surface. The postprocessing methods, such as IPL flashing and corona treatment, increased surface roughness and facilitated the transport of ionic species and ROS (Jeong et al, 2021). Overall, with the developed coating compositions and the postprocessing methods, antibacterial coatings with different microbicidal mechanisms were achieved with the capability to kill microbes quickly on contact.…”
Section: Antimicrobial Effectmentioning
confidence: 99%